Hysteroscopy does not increase the risk of microscopic extrauterine spread in endometrial carcinoma. Issue 2 (1st February 2003) - Selvaggi, L.; Cormio, G.; Ceci, O.; Loverro, G.; Cazzolla, A.; Bettocchi, S.
Abstract : Fluid hysteroscopy has been suspected to cause tumor dissemination in the abdominal cavity in endometrial cancer patients. The aim of our study was to evaluate the incidence of microscopic extrauterine spread according to diagnostic modality (dilatation & curretage, D&C, hysteroscopy, or both) in patients with endometrial carcinoma. A retrospective study was conducted on 147 patients with histologically proven diagnosis of endometrial carcinoma without macroscopic extrauterine disease. Fluid hysteroscopy was performed by using saline solution irrigated at a final flow of 150 ml/min with a intrauterine pressure ranging between 25 and 50 mmHg. Microscopic intraperitoneal disease and positive peritoneal cytology were considered the primary end-points of this analysis. Fifty-two patients (35%) had diagnosis of endometrial cancer made only by D&C, 56 (39%) underwent D&C and then hysteroscopy, and 39 (26%) had only hysteroscopy. Distribution of the patients in this three groups was casual, and clinicopathologic characteristics of the patients in the three groups were similar. Peritoneal cytology was positive in nine patients, 13 had microscopic ovarian metastases, and eight had microscopic involvement of the pelvic peritoneum or of omentum. Neither the presence of positive peritoneal cytology nor the findings of microscopic intraperitoneal dissemination were significantly associated with the diagnostic procedure employed for primary diagnosis (D&C or D&C plus hysteroscopy or hysteroscopy alone). We conclude that fluid hysteroscopy does not increase the risk of microscopic intraperitoneal spread in endometrial cancer patients as compared to D&C.